PENELITIAN DAN PENGEMBANGAN PADA MATA PELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK - Arief, Hafid; Pamungkas, Aan Subhan; Alamsyah, Trian Pamungkas (Jurnal Pendidikan Dasar, 2023)
This study aims to develop animated video learning media to improve students' initial reading skills at SDN Serang 21. This study uses Research and Development (RnD) research using the ADDIE model (Analysis, Design. Development, Implementation, Evaluation). The subjects of this study were 22 first grade students at SDN Serang 21. The data in this study were collected through observation, interviews, questionnaires and tests. The data analysis performed was quantitative and qualitative. The results of the study obtained an average value of expert validation with a proportion of 85.9% which was included in the "Very Eligible" category, the average score of student responses obtained a proportion of 95% which was included in the "Very Good" category, and the average test score students' understanding obtains a proportion value of 95% which is included in the "Very Good" category. Thus, it can be concluded that this animated video learning media can be used in learning and is suitable to be used as a learning medium to improve beginning reading skills.